Towards a Unified Mathematical Data Infrastructure: Database and Interface Generation - Bercic, Katja; Kohlhase, Michael; Rabe, Florian (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2019)
Data plays an increasing role in applied and even pure mathematics: datasets of concrete mathematical objects proliferate and increase in size, reaching upÂ to 1Â TB of uncompressed data and millions of objects. Most of the datasets, especially the many smaller ones, are maintained and shared in an ad hoc manner. This approach, while easy to implement, suffers from scalability and sustainability problems as well as a lack of interoperability both among datasets and with computation systems. In this paper we present another substantial step towards a unified infrastructure for mathematical data: a storage and sharing system with math-level APIs and UIs that makes the various collections findable, accessible, interoperable, and re-usable. Concretely, we provide a high-level data description framework from which database infrastructure and user interfaces can be generated automatically. We instantiate this infrastructure with several datasets previously collected by mathematicians. The infrastructure makes it relatively easy to add new datasets.
CRIS-Team Scopus Importer:2019-07-26